2012
DOI: 10.5754/hge11964
|View full text |Cite
|
Sign up to set email alerts
|

p53 and p73 Expression in Esophageal Carcinoma Correlate with Clinicopathology of Tumors

Abstract: Increased expression of p53 and p73 in esophageal carcinoma may serve as an indicator of tumor severity. Detection of these proteins in future studies may help understand the mechanisms of development, invasion and metastasis in esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Similarly, Liu et al [8] also reported that TP73 was overexpressed in cervical cancer tissues compared with normal cervical tissues. In addition, high expression of TP73 was suggested in several kinds of human tumors such as breast cancer [15,16], esophageal cancer [17], thymic carcinoma [18], extrahepatic bile duct carcinoma [19], cholangiocellular carcinoma [20], hepatocellular carcinoma [21,22], gastric cancer [23,24], colorectal cancer [25–27], ovarian cancer [28], laryngeal cancer [29], parotid gland carcinoma [30], cutaneous melanoma [31] and retinoblastoma [32]. However, low TP73 expression was observed in bladder cancer and head and neck squamous cell carcinoma, compared to corresponding normal tissues [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al [8] also reported that TP73 was overexpressed in cervical cancer tissues compared with normal cervical tissues. In addition, high expression of TP73 was suggested in several kinds of human tumors such as breast cancer [15,16], esophageal cancer [17], thymic carcinoma [18], extrahepatic bile duct carcinoma [19], cholangiocellular carcinoma [20], hepatocellular carcinoma [21,22], gastric cancer [23,24], colorectal cancer [25–27], ovarian cancer [28], laryngeal cancer [29], parotid gland carcinoma [30], cutaneous melanoma [31] and retinoblastoma [32]. However, low TP73 expression was observed in bladder cancer and head and neck squamous cell carcinoma, compared to corresponding normal tissues [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Bahnassy et al (2005) and Huang et al (2014) found that high p53 expression was associated with a poor survival rate in ESCC patients [ 42 , 43 ]; and Han et al (2007) showed that p53 expression was positively correlated with tumor stage and lymph node metastasis [ 44 ]. Ye et al (2012) reported that p53 expression was not associated with the gender or age of the patient, but was associated with tumor differentiation degree and lymph node metastasis [ 45 ]. A retrospective cohort study of 136 ESCC patients, conducted to investigate the prognostic role of p53 in patients with ESCC suggested that overexpression of this protein was associated with poor prognosis in these patients, and it’s a significantly independent predictor of poorer overall survival ( p = 0.04) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 Other studies have also shown overexpression of p53 protein in normal tissue adjacent to tumor or preneoplastic lesions in various cancers. 28,29 The association of p53 expression by IHC with the LOH for the p53 gene (D17S786) was, however, only modest. In LOH+ cases, overexpression of the p53 protein was seen in most of the cases.…”
Section: Association Of Ihc With Lohmentioning
confidence: 98%